A novel HLA allele, HLA‐B*37:06:02, identified in a Chinese family. Issue 5 (12th September 2014) - Li, X.; Zou, H.; Gu, B.; Zhu, Y.; Chen, Q.
<x xml:space="preserve">Abstract</x> The novel allele HLA‐B*37:06:02 differs from HLA‐B*37:06:01 by a silent nucleotide substitution at codon 47P.